2017
DOI: 10.1016/j.asr.2016.10.020
|View full text |Cite
|
Sign up to set email alerts
|

The use of PSD analysis on BeiDou and GPS 10 Hz dynamic data for change detection

Abstract: This paper examines the use of GPS and BeiDou data to measure the movements of two oscillating platforms in a series of field experiments. Data were gathered from a variety of GNSS receivers at a rate of 10Hz, and processed in an on the fly manner, resulting in 3D coordinates at a 10Hz rate with the corresponding precise time. These data were then analysed using a Power Spectral Density (PSD) function to derive the frequency of the movements. The positional data were also compared by matching a 500 epoch secti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…High-rate GNSS relative positioning has been widely applied to problems in sports (Buchheit et al 2014, Hoppe et al 2018, earth sciences (Kouba 2003, Larson et al 2003, Genrich and Bock 2006, Grapenthin and Freymueller 2011 and civil engineering (Lovse et al 1995, Psimoulis et al 2008, Moschas and Stiros 2011, 2015, Im et al 2013, Kaloop and Kim 2014, Roberts and Tang 2017. We have extended high-rate GNSS positioning to high-rate GNSS attitude determination with particular attention to the current stateof-the-art multi-GNSS systems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High-rate GNSS relative positioning has been widely applied to problems in sports (Buchheit et al 2014, Hoppe et al 2018, earth sciences (Kouba 2003, Larson et al 2003, Genrich and Bock 2006, Grapenthin and Freymueller 2011 and civil engineering (Lovse et al 1995, Psimoulis et al 2008, Moschas and Stiros 2011, 2015, Im et al 2013, Kaloop and Kim 2014, Roberts and Tang 2017. We have extended high-rate GNSS positioning to high-rate GNSS attitude determination with particular attention to the current stateof-the-art multi-GNSS systems.…”
Section: Discussionmentioning
confidence: 99%
“…Most of engineering and sports' applications are based on GNSS precise relative positioning, often aided with sensors such as accelerometers, magnetometers and gyros. In civil engineering applications, high-rate GNSS precise positioning has been applied to monitor dynamic deformation of tall structures/buildings and bridges (Lovse et al 1995, Kijewski-Correa et al 2006, Meng et al 2007, Psimoulis et al 2008, Moschas and Stiros 2011, Moschas and Stiros 2015, Im et al 2013, Kaloop and Kim 2014, Roberts and Tang 2017. When aided with low cost micro-electro-mechanical system (MEMS), highrate GNSS precise positioning can be used to provide precise positioning for aircrafts (Bischof and Schön 2017) and to continuously measure positions, velocities, and other movement information on athletes and pedestrians in sports-related applications (Waegli andSkaloud 2009, Morrison et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…By means of numerous zero‐baseline experiments, Tang et al verified that the GPS‐L1‐only precision is better than the GPS‐L2‐only precision, that GPS‐L2‐only precision closely resemble the BDS B1, B2, and B3, and that the integrated GPS/BDS precision is better than the GPS‐only precision. Roberts et al conducted two groups of experiments simulating real movements on a dynamic structure on two platforms (Figure ) for the purpose of analyzing and evaluating the performance of integrated GPS/BDS system. The experiment results indicated that the integrated GPS/BDS solution can improve the positioning precision in three directions, especially the vertical direction.…”
Section: Combination Of Gps and Other Gnss Constellationsmentioning
confidence: 99%
“…Two oscillating platforms simulating real structural vibrations, that is, the bungee experiment devices (left) and the rotating arm rig (right)…”
Section: Combination Of Gps and Other Gnss Constellationsmentioning
confidence: 99%
See 1 more Smart Citation